Rituximab therapy in pulmonary alveolar proteinosis improves alveolar macrophage lipid homeostasis - Malur, Anagha; Kavuru, Mani S; Marshall, Irene; Barna, Barbara P.; Huizar, Isham; Karnekar, Reema; Thomassen, Mary Jane (My University, 2012)
Pulmonary Alveolar Proteinosis (PAP) patients exhibit an acquired deficiency of biologically active granulocyte-macrophage colony stimulating factor (GM-CSF) attributable to GM-CSF specific autoantibodies. PAP alveolar macrophages are foamy, lipid-filled cells with impaired surfactant clearance and markedly reduced expression of the transcription factor peroxisome proliferator-activated receptor gamma (PPARγ) and the PPARγ-regulated ATP binding cassette (ABC) lipid transporter, ABCG1. An open label proof of concept Phase II clinical trial was conducted in PAP patients using rituximab, a chimeric murine-human monoclonal antibody directed against B lymphocyte specific antigen CD20. Rituximab treatment decreased anti-GM-CSF antibody levels in bronchoalveolar lavage (BAL) fluid, and 7/9 patients completing the trial demonstrated clinical improvement as measured by arterial blood oxygenation. This study sought to determine whether rituximab therapy would restore lipid metabolism in PAP alveolar macrophages. BAL samples were collected from patients pre- and 6-months post-rituximab infusion for evaluation of mRNA and lipid changes. Mean PPARγ and ABCG1 mRNA expression increased 2.8 and 5.3-fold respectively (p ≤ 0.05) after treatment. Lysosomal phospholipase A2 (LPLA2) (a key enzyme in surfactant degradation) mRNA expression was severely deficient in PAP patients pre-treatment but increased 2.8-fold post-treatment. In supplemental animal studies, LPLA2 deficiency was verified in GM-CSF KO mice but was not present in macrophage-specific PPARγ KO mice compared to wild-type controls. Oil Red O intensity of PAP alveolar macrophages decreased after treatment, indicating reduced intracellular lipid while extracellular free cholesterol increased in BAL fluid. Furthermore, total protein and Surfactant protein A were significantly decreased in the BAL fluid post therapy. Reduction in GM-CSF autoantibodies by rituximab therapy improves alveolar macrophage lipid metabolism by increasing lipid transport and surfactant catabolism. Mechanisms may involve GM-CSF stimulation of alveolar macrophage ABCG1 and LPLA2 activities by distinct pathways.
Keywords: PAP, Rituximab, Alveolar macrophages, Surfactant, PPARγ, ABCG1, LPLA2